Pharmacists’ Behaviour when Dispensing Liquid Prescription Medicine for Children: A Quantitative Study - Elashwah, Mohamed (Journal of Pharmacy Practice and Community Medicine)
Objectives: This study aims were to investigate community pharmacists’ behavior when dispensing a liquid prescription medicine for a child, and identify strategies used or recommended by pharmacists to optimize the dispensing procedure and minimize errors in dispensing. Methods: A direct observation (by a researcher) scenario-based role-play method was used. Twenty eight community pharmacies were visited in the inner city region of metropolitan Sydney, accessible to the University of Sydney, and 39 pharmacists were approached. Each pharmacist was visited 3 times with 2 different scenarios being role played during each visit. Participants received performance feedback from the researcher after each visit. Quantitative data were collected using a standardized data collection sheet, on the pharmacists’ responses to the scenarios. A score (researcher and pharmacist) was computed reflecting how the pharmacists dealt with each scenario in terms of dosage calculations, questioning and counseling. Results: Overall, some pharmacists scored poorly in the dosage calculation tasks, although for many, it appeared that this had improved over time and with researcher feedback. However, our study sample size was not large enough to monitor a statistically significant change in practice over time as a result of the visits and performance feedback. Conclusion: This study highlighted a potential gap in identifying and avoiding medication errors due to dose calculations for ambulatory children, which may also be similar for hospital pediatric patients. Accordingly, urgent need for methods to improve such MEs by decreasing the possibility of errors due to dose calculation is a must.
Keywords: Child behaviour; Community pharmacist; Dispensing errors; Liquid; Pharmacists; Procedure; Quantitative; Strategies